2018
DOI: 10.1590/fst.27517
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for obtaining collagen from chicken feet and its characterization

Abstract: The objective of this study was to extract collagen from chicken feet, determining optimal extraction conditions according to acetic acid concentration, pepsin content and time of enzymatic hydrolysis. A factorial design 2 3 was used, with three replications at the central point, totaling 11 experiments. The response variable studied was the collagen content of the isolate obtained. In addition to the optimization, the characterization of the isolates with higher and lower collagen content, in relation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…NaCl, acetic acid, and pepsin are used to hydrolyze non-collagenous protein at cross-linking sites. The yield of collagen mostly depends on the acetic acid concentration, pepsin content, and duration of hydrolysis ( Araújo et al., 2018 ). Nagai and Suzuki (2000) reported that acetic acid (0.5 M) could be used to extract collagen from skin and fins of fishes; whereas bone collagen could be decalcified with 0.5 M EDTA (ethylenediaminetetraacetic acid).…”
Section: Production Of Biopolymers From Different Food Wastesmentioning
confidence: 99%
“…NaCl, acetic acid, and pepsin are used to hydrolyze non-collagenous protein at cross-linking sites. The yield of collagen mostly depends on the acetic acid concentration, pepsin content, and duration of hydrolysis ( Araújo et al., 2018 ). Nagai and Suzuki (2000) reported that acetic acid (0.5 M) could be used to extract collagen from skin and fins of fishes; whereas bone collagen could be decalcified with 0.5 M EDTA (ethylenediaminetetraacetic acid).…”
Section: Production Of Biopolymers From Different Food Wastesmentioning
confidence: 99%
“…Consequently, obtaining collagen and hydrolysates from this raw material would add considerable value to this waste. Some studies have shown promisingly the extraction of collagen and hydrolyzed from chicken slaughter residues, such as feet (Araújo et al, 2018;Chakka et al, 2017), skin (Aksun Tümerkan et al, 2019;Dechsle et al, 2016), bones (Dechsle et al, 2016), among others, however chicken CMS residue has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of collagen from the cartilage of aquatic and terrestrial animals has been the object of study by researchers (Gómez-Guillén et al, 2011;Simões et al, 2014;Araújo et al, 2018) to identify bioactive compounds derived from cartilage with potential beneficial health properties. However, only one study published by Losso & Dgawa (2014) has focused on the extraction of collagen from chicken keel bone cartilage and its thermal stability.…”
Section: Introductionmentioning
confidence: 99%